A Vocabulary and Its Vicissitudes: Notes towards a Memoir. Issue 2 (July 2015) - Mehlman, Jeffrey
<x xml:space="preserve">Abstract</x> A series of reflections on Laplanche and Pontalis's Vocabulaire de la psychanalyse, one of the precursor volumes of the Dictionary of Untranslatables, and specifically on Laplanche's effort to glean the most important lessons to be culled from that speculative volume on the translation of German into French. Laplanche, in Vie et mort en psychanalyse, posits that, until one gauges the significance of the chiasmus structuring the evolution of Freud's metapsychology, the sense of Freud's discovery will not have been grasped. In this essay, the translator of Vie et mort uncovers the chiasmus that structures the evolution of Laplanche's own thought and reflects on the role which that figure has played in his own career as a critic.